Human Serum Albumin Is an Essential Component of the Host Defense Mechanism Against Clostridium difficile Intoxication. (2nd June 2018) - di Masi, Alessandra; Leboffe, Loris; Polticelli, Fabio; Tonon, Federica; Zennaro, Cristina; Caterino, Marianna; Stano, Pasquale; Fischer, Stephan; Hägele, Marlen; Müller, Martin; Kleger, Alexander; Papatheodorou, Panagiotis; et al.
Abstract: Background: The pathogenic effects of Clostridium difficile are primarily attributable to the production of the large protein toxins ( C difficile toxins [Tcd]) A (TcdA) and B (TcdB). These toxins monoglucosylate Rho GTPases in the cytosol of host cells, causing destruction of the actin cytoskeleton with cytotoxic effects. Low human serum albumin (HSA) levels indicate a higher risk of acquiring and developing a severe C difficile infection (CDI) and are associated with recurrent and fatal disease. Methods: We used a combined approach based on docking simulation and biochemical analyses that were performed in vitro on purified proteins and in human epithelial colorectal adenocarcinoma cells (Caco-2), and in vivo on stem cell-derived human intestinal organoids and zebrafish embryos. Results: Our results show that HSA specifically binds via its domain II to TcdA and TcdB and thereby induces their autoproteolytic cleavage at physiological concentrations. This process impairs toxin internalization into the host cells and reduces the toxin-dependent glucosylation of Rho proteins. Conclusions: Our data provide evidence for a specific HSA-dependent self-defense mechanism against C difficile toxins and provide an explanation for the clinical correlation between CDI severity and hypoalbuminemia. Abstract : We demonstrated that HSA inactivates Clostridium difficile toxins in vitro and in vivo, thus protecting from intoxication. This self-defense mechanism might explain the correlation between hypoalbuminemia and susceptibility to C difficile infection and could lead to novel therapies against CDI.